Responding to global disruption: the Covid-19 impact on the portuguese textile and clothing industry - Cabral, Maria Madalena Cardoso Dias de Brito (2022)
The Covid-19 pandemic created unprecedented disruptions to supply chains and manufacturing firms globally. In this context, the Portuguese Textile and Clothing Industry, known for its expertise and high-quality as a cluster, has also been challenged and called upon to adapt and further evolve. As recent observations within the Portuguese manufacturing are limited to the surface impact level of this crisis (i.e macroeconomic impact), this dissertation seeks to fill this gap by focusing on firms’ individual ability to respond within international disruptive environment. The key objective was to explore the Portuguese Textile and Clothing Industry response, in particular aiming to understand how this industry overcame the initial challenges and grasped possible opportunities encountered with the pandemic. The concepts of dynamic capabilities and risk management presented a theoretical starting point for the study, and Semi- structured interviews were conducted with eight Portuguese firms in the TCI. The results found that flexibility, customization and transparency were determinant aspects that led to a positive response. Through the challenges, some opportunities for future development also appeared, namely the opportunity for innovation and sustainability investments, which impacted companies’ performance, even within a crisis setting. Further, it was felt that the potential for collaborations had not been fully explored. It is expected that the results of this study can contribute not only to the growing body of knowledge on companies’ responses to a scenario without precedent, but also to companies’ own development and continued adaptation to these circumstances on a practical, operational and possibly even strategic level.